Cosmic odyssey - Heidmann, Jean (Cambridge University Press, 1989)
The immensity of the cosmos, the richness of the Universe, the limits of space and time: these are the themes of Cosmic Odyssey, which takes the reader on imaginary journeys through the past, present and future of our universe.